Pre-Marriage Conflict for Bride and Groom: A Case Study at Jekan Raya Religious Affairs Office of Palangka Raya City - Desi Desi; Arini Safitri; Ihsan Mz; Desi Erawati (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2023)
In fact, every human who wants to marry surely desires peaceful, happy and intact life. All effort was done in order to get happiness in marriage. However, to create such things, people face some obstacles like conflict. This study was aimed at exploring conflicts and factors becoming the reasons for the conflict of the bride and groom at the Religious Affairs Office (KUA) Jekan Raya. This study applied a qualitative descriptive approach with interview, observation and documentation as data collection techniques. The primary data sources were five people who are candidate bride and groom who registered at the Religious Affairs Office (KUA) of Jekan Raya. To analyze data, it was used conflict types theory from Sadarjoen and conflict causal factors according to Sofyan Wilis’s theory. The result revealed that there was a couple that can be categorized as Zero Sum and Motive conflict type because of selfish behaviour. Then, there were five couples having conflict type category Personality Based and Situational Conflict. It was evidenced that there was a different character for each couple. Additionally, there were three couples having Basic-Non-Basic Conflict type since the situation changed which created conflict. Meanwhile, factors becoming conflict sources were lack of communication, as seen in four married couples, egocentrism as found in one married couple, and different opinions as found in five married couples. Additionally, an economic problem happened in one married couple, and a misunderstanding occurred in five married couples.